Comparative Analysis of Malaysian and Indonesian Retirement Plan - Shah, Nurin Athirah Mohd Alam; Nasrul, Muhammad Amrullah; Rahman, Siti Fatimah Binti Abd.; Seviyana, Devi (Lex Scientia Law Review, 2023)
In Malaysia, the Employee Provident Fund (EPF) was established Under the Employees Provident Fund Act 1991 as a social security organisation that offers members trustworthy and efficient savings management and it is open to both personnel. In contrast, the Private Pension Administrator (PPA) developed the Private Retirement Scheme (PRS), a retirement programme, to address retirees' insufficient resources for meeting their retirement expenses in light of rising living standards and longer life expectancies. Having to see the similar aspects between EPF and PRS in terms of creating savings and their importance towards securing a certain degree of comfort for retirees, the purpose of this study is to provide a thorough explanation of how these two retirement plans can benefit all Malaysian private employees. Similar to Malaysia, all private sector workers in Indonesia are also required to participate in retirement plan. Thus, the purpose of this study is to evaluate the similarities and differences between Malaysia's and Indonesia's retirement plan. This research employs a qualitative approach, by conducting library-based research on the relevant materials including, but not limited to statutory provisions, case laws, law textbooks, journal articles, newspapers, conference proceedings, and seminar papers. At the end of the discussion, the findings show that both countries have their own retirement plans and have the same goal which is to provide facilities to all private-sector workers.